Perlindungan Perempuan Melalui Perjanjian Pra Nikah (Respon Terhadap Isu Hukum dan Gender) - Muhammad Ngizzul Muttaqin; Miftah Rosadi (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2020)
Facing problem and misunderstanding in family becomes a necessity and humane. The goal of harmonious and happy family is a necessity and an order from the law. One of the mandates given by the law in order to overcome problems in the household is the “marriage agreement”. In the contemporary era, marriage agreements are needed in order to protect the interests of women. Where women in contemporary gender issues have the same roles and abilities as men. This study uses descriptive-qualitative analysis through library research, where this paper seeks to reveal the importance of prenuptial agreements as an effort to protect women’s interest in response to contemporary law and gender issues. The findings in this study indicates that women’s protection can be minimized and anticipated by prenuptial agreements. While in legal and gender issues, prenuptial agreements can be done before and after marriage to regulate all the things needed by both parties eliminate discrimination and oppression of women.